RETRACTED: Organization of practical training in higher engineering education - Gritsay Dmitry; Krekova Marina; Parsieva Larisa; Ivashova Valentina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001